Antioxidant Protection of Donor Packed Red Blood Cells using Mexidol - D.V., Gavryuchenkov; I.V., Fedoseykin; V.E., Kosachev; V.A., Shapovalova; E.N., Dinov; Y.E., Dinova; I.A., Nikiforov; A.G., Merkin (Journal of Antioxidant Activity, 2018)
The current research shows the possibility of long-term conservation of the erythrocytes an-tioxidant activity in the process of donor packed red blood cells while introducing mexidol to the hemoconservant glugicir composition.
Keywords: hemoconservants; peroxygenation; glugicir